Vehicle Routing and the Value of Postponement - Asim, Muhammad (2008)
Industrial wisdom presumes that postponing the collection (or delivery) services reduces the transportation cost & most of the studies conducted in practical scenarios also substantiate this belief. However there is a dearth of in-depth research assessing the value of postponement in vehicle routing context. This research aims to explore the significance of postponement & its inter-relationship with related problem parameters such as vehicle capacity, clients' density, location of clients & depot, clients' demand, postponement level etc.